HASIL BELAJAR IPS TENTANG MENGENAL TEMPAT-TEMPAT KEGIATAN EKONOMI MELALUI METODE KARYA WISATA ANAK TUNAGRAHITA RINGAN - SETYARINI, SULIS (Jurnal Pendidikan Khusus, 2015)
Abstract : There are several difficulties faced by mild-mental-retarded students in a social learning on the aspect of economic activity places. The field trip method is applied as a learning strategy with 70% success indicator. The research is aimed to (1) describe the activities of children in learning the material social studies to know places of economic activity with a field method is used; (2) describe the learning outcome social studies on the material to know the places of economic activity with the  4 mild mental retarded children in elementary special school of Banyuwangi through the field trip method. The research method used was a class action research applying Kemmis model with include observation and test collection method. Based on of the research, the result on first cycle was less satisfied. The average value of child’s activities is 52,9% achieved, and the average value of 57,5% of children's learning outcomes. The second cycle result was the average value of chold’s activities is 68,8%, achieved, and the learning outcomes of children reached 76,25%. It showed the average result of the child's learning outcomes specified above the defined minimum completeness criteria, which was 70 and above, achieved. The conclusion stated is the application of a field trip method can improve learning outcomes social studies on to know material places the economic activities of mild mental retarded children in elementary special school of Banyuwangi. Keywords : learning outcomes, methods of field trips